Needs, trends, and advances in scintillators for radiographic imaging and tomography - Wang, Zhehui; Dujardin, Christophe; Freeman, Matthew S.; Gehring, Amanda E.; Hunter, James F.; Lecoq, Paul; Liu, Wei; Melcher, Charles L.; Morris, C. L.; Nikl, Martin; Pilania, Ghanshyam; Pokharel, Reeju; et al. (IEEE transactions on nuclear science, 2023)
Radiographic imaging and tomography (RadIT), which started with Röntgen's seminal X-ray work in 1895, now include an increasing number of imaging and tomography (IT) modalities. In addition to the original absorption-based X-ray radiography, others include phase contrast X-ray imaging, coherent X-ray diffractive imaging, MeV X- and γ-ray radiography, X-ray computed tomography, proton IT, neutron IT, positron emission tomography (PET), high-energy electron radiography, and cosmic-ray muon tomography. Scintillators are widely used in RadIT as the detector frontend that converts ionizing radiation into signals and data. We give an overview of the status and needs of scintillator applications in RadIT. More than 160 kinds of scintillators were presented during the SCINT22 conference, and offered ample options for novel RadIT applications. New trends in scintillators for RadIT applications include inorganic and organic scintillator composites or heterostructures, liquid phase synthesized perovskites and single-crystal micrometer-thick films, use of multi-physics models and data science to guide scintillator and RadIT optimization, structural innovations such as photonic crystals, nano-scintillators enhanced by the Purcell effect, heterostructural scintillating fibers, and multilayer configurations. RadIT have also been recognized as powerful tools for scintillator discovery and development.